Environment-related awareness and behaviors of children ages six to eight years - Fernandez, Kriscile Princess C.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
This exploratory research investigated the environment-related awareness and behaviors (ERAB) of children ages six to eight years. A total of 60 randomly selected children from the urban (Brgy. Culiat, Quezon City, Metro Manila) and sub-urban locales (Brgy. Model, Puerto Princesa City, Palawan) participated in the study using a qualitative research design. Data were gathered initially through drawings of children, followed by individual in-depth interviews with them, their parents, and the community officials of their respective barangay.Transcribed data were analyzed according to common themes and were validated with the help of two experts on environment and children. Majority of the children across genders and locales perceived the environment as composed of everything surrounding them. They were aware that the environment is important for the beautification of the surroundings, for the prevention of environment destruction, and for the survival of living organisms. They also showed awareness that pollution destroys the environment and that negative outcomes would happen in the future if people would continue to destroy the environment.Most children also performed various environment-friendly behaviors at home, in school, and in the community. These behaviors primarily help in maintaining the cleanliness of the environment. The home appeared to be the most significant context from which the children acquire ERAB.Children acquire ERAB through a variety or ways such as by observation, direct instruction, experience, and participation in the environment-related programs of the community. The study recommends that environmental partners consider the significant role and contribution of the parents (and other socializing agents at home) in the children's acquisition of ERAB.
Submitted October 2013
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Children -- Philippines; Children and the environment -- Philippines; Children -- Conduct of life